South Sudan Economic Update, July 2018 - World Bank (World Bank, Washington, DC, 2018)
Real GDP is projected to further contract by 3.5 percent in FY2018, following the contraction of about 6.9 percent in FY 2017. Monetization of the fiscal deficit led to strong money growth and high inflation, although there are indications that borrowing from the Bank of South Sudan had been limited in the second half of 2017. The spread between the official and the parallel market exchange rates remains wide, despite the recent exchange rate appreciation. 82 percent of South Sudanese were living under the international poverty line in 2016. High inflation, disrupted trade flows, and conflict continue to expose many households to food insecurity and displacement. South Sudan's cabinet approved the general budget for fiscal year 2018/19, which increased by about 60 percent to reach 584 million USD up from 366 million USD in FY17/18. It remains unclear how South Sudan will finance the budget, given its struggling economy amidst the ever-rising inflation and conflict. Spending continues to be skewed toward defense at the expense of poverty reduction.